2016
DOI: 10.1177/0013916516653638
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Acceptance of Nature-Preservation-Related Restrictions as the Result of the Compensatory Effects of Environmental Attitude and Behavioral Costs

Abstract: Personal costs that accompany nature-preservation-related restrictions hurt their acceptance, irrespective of whether individuals care about environmental protection or not (i.e., irrespective of people’s environmental attitude). Analogically, people’s environmental attitude unconditionally determines their acceptance of nature-preservation-related restrictions, irrespective of the costs. This view stands in contrast to the typical NIMBY (not-in-my-back-yard) research in which people’s environmental attitude i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 39 publications
2
26
2
1
Order By: Relevance
“…The scale is calibrated as a Rasch scale using the marginal maximum likelihood method. The reliability of the attitude scale was somewhat lower in Study 1 (relps= .70, α = .64) than in other studies which have employed GEB (e.g., Byrka et al, 2017; see also Kaiser et al, 2010 for a recent review).…”
Section: Environmental Attitudecontrasting
confidence: 53%
“…The scale is calibrated as a Rasch scale using the marginal maximum likelihood method. The reliability of the attitude scale was somewhat lower in Study 1 (relps= .70, α = .64) than in other studies which have employed GEB (e.g., Byrka et al, 2017; see also Kaiser et al, 2010 for a recent review).…”
Section: Environmental Attitudecontrasting
confidence: 53%
“…People with pro-environmental beliefs were modeled as engaging in pro-environmental behaviors; for instance, being more likely to start recycling (an inexpensive change) than to reduce driving or flying (a costly change). Likewise, O'Connor et al's (2002) Pennsylvania survey found respondents willing to engage in money-saving pro-environmental behaviors like buying energy efficient devices, but less willing to try harder actions, such as installing solar panels (see also Byrka et al, 2017). Policies implying more direct costs, such as barrier building, generally have lower public support, according to Bostrom et al's (2012) finding that "inexpensive" environmental policies are largely favored over costlier ones.…”
Section: Increased Support For a Fossil Fuel Phaseout But Reduced Sumentioning
confidence: 99%
“…The only factor that significantly predicted the likelihood of a person supporting PAs in Amapá was place of residence, despite the profile differences found between our rural and urban populations. The difference between urban and rural populations regarding public support for PAs has been reported in the literature (e.g., Carrus et al 2005, Triguero-Mas et al 2010, Byrka et al 2017. The most common explanation for this pattern is that urban populations, on average, have more education and better incomes; thus, they are more aware of global environmental problems and are more likely to exhibit pro-environmental attitudes (Huddart-Kennedy et al 2009, Lo 2014.…”
Section: Discussionmentioning
confidence: 91%
“…Gender seems to matter as well: for instance, Allendorf and Allendorf (2013) found that, among rural populations in Myanmar, women are less likely to have a positive attitude towards PAs than men, possibly because they are less informed about wildlife, the non-economic benefits that PAs can provide and PA management. Place of residence has been found to be relevant because the livelihoods of people living inside or near PAs are usually affected by regulations set by state agencies (Holmes 2013), so they are expected to show less support for environmental conservation than people living in other rural areas or in urban areas (Triguero-Mas et al 2010, Bragagnolo et al 2016, Byrka et al 2017. Finally, cultural factors, such as place attachment (i.e., the existence of emotional and cognitive bonds with a place), can also play a role.…”
Section: Introductionmentioning
confidence: 99%